Reflections on the Inter-American System for the Protection of Human Rights in a Contentious Case Concerning the Application of the Death Penalty - Huerta Guerrero, Luis Alberto (2004)
The judgments of international courts, such as the Inter-American Court of Human Rights, not only guarantee the protection of fundamental rights, but also provide an insight into the functioning of the Inter-American system for the protection of human rights. The examination of this case not only provided insights into the death penalty imposed on 31 persons under the Crimes Against the Person Act enacted by the respondent State, but also reflected on the procedure of these cases before the Inter-American Court to address human rights violations. The author evaluates the preliminary objections, provisional measures, the procedural institution of joinder of cases, and the judgment on the merits. This analysis is intended to reflect, in addition to the previously mentioned issues, the crucial work of the Inter-American Court in the context of the Inter-American system.